Type-specific step characteristics of sprinters during acceleration phase of 100-m race - Naito, H.; Kariyama, Y.; Miyashiro, K.; Yamamoto, K.; Tanigawa, S. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study was to show the type-specific step characteristics during acceleration phase (0-30 m) of a 100-m race. Fifty-nine male varsity sprinters (10.68 ± 0.22 s) were recorded running in 100-m races using 10 high-speed cameras, and step variables in 0-30 m and maximum speed phase (MSP, 30-60 m) were calculated. Cluster analysis was used to classify the subjects into the step-frequency (SF) or -length (SL) reliant group (i.e., type-specific) as indicators for the ratio of the SF and SL in the MSP. Then, each group was divided into two sub-groups according to the mean speed in MSP (good and poor sprinters). As a result, the sprinters were classified into SL-, SF-, and Mid-groups. In SL-group, good sprinters showed a longer SL from the 7th step to MSP than the poor sprinters. In SF-group, good sprinters showed a higher SF from the 7th step to MSP than the poor sprinters.